Correlation between whole salivary prostaglandin E2 and hemoglobin A1c levels among type-2 diabetic and non-diabetic patients with periodontal inflammation - Marwa Y. Shaheen; Amani M. Basudan; Abeer S. Alzawawi; Fatemah Al-Ahmari; Hajer A. Aldulaijan; Nouf Alshibani; Rakan Saifuddin Shaheen; Reem Al-kattan (BMC, 2024)
Abstract Background It is hypothesized that whole salivary prostaglandin E2 (PgE2) levels are higher in patients with type-2 diabetes mellitus (type-2 DM) than non-diabetic individuals with periodontal inflammation; and that whole salivary expression of PgE2 is correlated with hemoglobin A1C (HbA1c) levels. The aim of the present study was to compare whole salivary PgE2 levels among patients with type-2 DM and non-diabetic individuals with periodontal inflammation. Methods Sociodemographic data, duration since the diagnosis and management of type-2 DM, most recent hemoglobin A1C (HbA1c level), and any familial history of DM was retrieved from patient's healthcare records. Participants were divided into four groups: Group-1: type-2 diabetics with periodontal inflammation; Group-2: type-2 diabetics without periodontal inflammation; Group-3: non-diabetics with periodontal inflammation; and Group-4: non-diabetics without periodontal inflammation. Plaque and gingival indices (PI and GI), probing depth (PD), clinical attachment loss (CAL) and marginal bone loss (MBL) were measured. Unstimulated whole saliva samples were collected and PgE2 levels were measured. Group-comparisons were done and P < 0.05 were considered statistically significant. Results One-hundred-sixty individuals were included. Mean HbA1c levels were higher in Group-1 than groups 2 (P < 0.05), 3 (P < 0.05) and 4 (P < 0.05). The PI (P < 0.05), GI (P < 0.05) and PD (P < 0.05) were higher in Group-1 than groups 2 and 4. The CAL was higher in Group-1 than groups 2 (P < 0.05) and 3 (P < 0.05). The PD (P < 0.05), PI (P < 0.05) and GI (P < 0.05) were higher in Group-3 than Group-4. The MBL was higher in Group-1 than groups 2 (P < 0.05), 3 (P < 0.05) and 4 (P < 0.05). The PgE2 levels were higher in Group-1 than groups 2 (P < 0.05), 3 (P < 0.05) and 4 (P < 0.05). Conclusion Hyperglycemia in patients with type-2 DM is associated with increased expression of whole salivary PgE2 levels and worsened periodontal inflammation compared with individuals with well-controlled type-2 DM and non-diabetic individuals.